Online to offline sales method in the e-commerce industry in denpasar - Subawa, Nyoman Sri; Budiadnyana, I Wayan Agus (Journal of Business on Hospitality and Tourism, 2021)
The purpose of this study is to determine the use of the online to offline (O2O) sales method in the e-commerce industry in Denpasar and to know the application of online to offline (O2O) can increase trust in e-commerce. The research design used in this study is a qualitative approach. The data collection techniques used were observation, interview, and documentation. The results of this study indicate the use of the online to offline sales method has many benefits if it is supported by adequate facilities and infrastructure, besides that the selection of offline stores must also be strategic.   to facilitate customers to take goods that have been ordered online, in this study it was found that the sales method online to offline can answer any doubts of consumers and change the social status of e-commerce. Using online to offline service dimensions in the form of physical evidence, reliability, responsiveness, assurance, and empathy can increase consumer confidence in e-commerce.